Little Legends : The Spell Thief - Percival, Tom, 1977- (London : Macmillan Children's Books, 2015)
"Jack (of the beanstalk fame) and his magical talking chicken, Betsy, have always been great at making new friends, like their BFFs Red and Rapunzel. But when Jack spots Anansi, the new kid in town, talking to a troll in the Deep Dark Woods, everything changes. Everyone knows that trolls mean trouble, and Jack will do anything to prove to the rest of his friends that Anansi is a troll spy. Even if that means using stolen magic!"--Provided by publisher.
4.5
3-6.
3-6
Keywords: Characters and characteristics in literature -- Juvenile fiction; Friendship -- Juvenile fiction; Magic -- Juvenile fiction; Characters in literature -- Fiction; Friendship -- Fiction; Magic -- Fiction; Characters and characteristics in literature -- Fiction; Friendship -- Juvenile fiction; Magic -- Fiction; Fantastic fiction